The brave one [videorecording (DVD)] - Jordan, Neil, 1950-; Foster, Jodie; Howard, Terrence; Katt, Nicky (Warner Home Video, 2008)
New York City radio host Erica Bain is working and living a wonderful life. One night she and her fiancé, David, are brutally attacked. David is killed and Erica is almost beaten to death. Erica is traumatized and in order to cope and work past the tragic event, Erica becomes someone else. She buys a gun and begins to roam the streets at night looking to take her revenge on the men who were responsible for the attack. Late one night, Erica is in the back of a convenience store when a man comes in and kills his store clerk wife. The man comes after her and she protects herself, finding that is very easy to shoot a gun. Days later, Erica is on the subway when she is about to be raped by two men, and again she protects herself. The city becomes fascinated with the exploits of this vigilante killer, but NYPD Detective Mercer is trying to catch this person, before the killer strikes again.